A two‐step protocol for isolation of influenza A (H7N7) virions and their RNA for PCR diagnostics based on modified paramagnetic particles. Issue 14 (1st June 2016) - Michalek, Petr; Dostalova, Simona; Buchtelova, Hana; Cernei, Natalia; Krejcova, Ludmila; Hynek, David; Milosavljevic, Vedran; Jimenez, Ana Maria Jimenez; Kopel, Pavel; Heger, Zbynek; Adam, Vojtech
Abstract : Annual epidemics of influenza cause death of hundreds of thousands people and they also have a significant economic impact. Hence, a need for fast and cheap influenza diagnostic method is arising. The conventional methods for an isolation of the viruses are time‐consuming and require expensive instrumentation as well as trained personnel. In this study, we modified the surface of nanomaghemite (γ‐Fe2 O3 ) paramagnetic core with tetraethyl orthosilicate and (3‐aminopropyl)triethoxysilane and the resulting particles were utilized for the isolation of H7N7 influenza virions. Consequently, we designed γ‐Fe2 O3 paramagnetic core modified with calcium tripolyphosphate which was employed for the isolation of viral nucleic acid after virion's lysis. Both of these procedures can be performed rapidly in less than 10 min and, in combination with the RT‐PCR, the whole influenza detection can be shortened to few hours. Moreover, the whole protocol could be easily automated and/or miniaturized, and thus can serve as a basis for use in a lab‐on‐a‐chip device. We assume that magnetic isolation is an exceptional procedure which can significantly accelerate the diagnostic possibilities of a broad spectrum of diseases.